Diseño de un relleno sanitario semi-mecanizado para el distrito de santiago de cao - la libertad 2015 - Pérez Calderón, Carlos Antonio (2016)
This research presents the design of a landfill Semi-machining for proper disposal of solid waste in the district of Santiago de Cao – La Libertad, conducting an analysis of the literature review, satellite images, documents and a situational analysis of the district. The study is aimed at mitigating pollution from municipal solid waste in the district, through the evaluation and analysis of technical criteria, description of engineering studies and environmental normativities line with force. The importance of this work is based, that a landfill is a complex and definitive method, given its ability to receive all types of solid waste and therefore contribute to reduce pollution to the environment and health of people. In various basic work methodology and technical studies were conducted, and different methods provided by the branch of health and environmental engineering, who served as information and basic parameters for the successful development of the project were used. From the results we can declare that the daily total solid waste generation district of Santiago de Cao is 21,117 tons / day, according to the daily generation of RR.SS. landfill design will be semi-mechanized type with a cumulative volume capacity 349676.30 cubic meters and requiring an area of approximately 10 hectares for a service life of 15 years according to the needs presented by the community and district